DEVELOPMENT OF ASSESSMENT HOTS (HIGHER ORDER THINKING SKILLS) BASED ON PROBLEM SOLVING IN SD/MI - Ulum, Anifa Rosari; Hidayah, Nurul; Yanti, Yuli (PD PGMI se Indonesia, 2021)
This research is motivated by the problems that occur, namely students have basically carried out a HOTS-based teaching and learning process or are oriented towards higher-order thinking skills, but during the evaluation process, the measuring instruments or questions used have not been able to measure students' high-level thinking skills. . The type of research to be conducted is Research and Development or R&D (Research and Development). This research refers to the Borg and Gall model which is limited to 7 stages from 10 initial stages, which include potentials and problems, data collection, product design, design validation, design revision, product testing and design revision. The instrument used is in the form of a rating scale to determine the feasibility of the product and to determine the response of educators and students to the feasibility and attractiveness of the product using a Likert scale. Data analysis was carried out, namely collecting data from the validation results of evaluation experts, material experts and language experts, educators and students of SD / MI. HOTS assessment based on problem solving which was developed